2021
DOI: 10.3390/biom11111633
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Mitochondrial Protein Defects in Neuromuscular Diseases

Abstract: Neuromuscular diseases (NMDs) are dysfunctions that involve skeletal muscle and cause incorrect communication between the nerves and muscles. The specific causes of NMDs are not well known, but most of them are caused by genetic mutations. NMDs are generally progressive and entail muscle weakness and fatigue. Muscular impairments can differ in onset, severity, prognosis, and phenotype. A multitude of possible injury sites can make diagnosis of NMDs difficult. Mitochondria are crucial for cellular homeostasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 314 publications
(313 reference statements)
0
4
0
Order By: Relevance
“…However, a significant number of them still need to be discovered. The functional identification of this group of proteins is of the utmost importance because their mutation can cause human diseases [32,63]. The biochemical characterization of these transporters facilitates their association with clinical alterations found in patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant number of them still need to be discovered. The functional identification of this group of proteins is of the utmost importance because their mutation can cause human diseases [32,63]. The biochemical characterization of these transporters facilitates their association with clinical alterations found in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a significant increase in Ser637 phosphorylation of DRP1 was found (Figure 5b), suggesting an alteration in mitochondrial shape. Fused mitochondria have been demonstrated in aging [33,34], under nutrient deprivation [35], and in neuromuscular disease [36,37]. In-depth morphological studies are necessary to verify the presence of fused/elongated mitochondria in SMA diaphragm.…”
Section: Energy Balance In Sma Diaphragmmentioning
confidence: 99%
“…The overall estimated prevalence of these disorders is one to three cases per 20,000 individuals [ 24 ], with lifelong symptoms that can appear from very early (newborn) to later in life. Unsurprisingly, mitochondrial disorders often affect organs with high metabolic needs such as muscles, heart, liver, kidneys, central nervous system (CNS), peripheral nervous system (PNS), as well sensory organs (eyes and ears) [ 13 , 25 ]. It has been reported that some mitochondrial disorders can affect only a single organ (as in Leber hereditary optic neuropathy (LHON) [ 26 ] and in mitochondrial non-syndromic hearing loss and deafness), but often, these disorders cause multi-system dysfunction.…”
Section: Introduction To Mitochondrial Disordersmentioning
confidence: 99%